Women in the coastal area and seaweed farming in Madura, East Java, Indonesia. Issue 1 (March 2021) - Sahidu, A M; Made, S; Riniwati, H
Abstract: This study aimed to 1) analyze the roles and tasks of female seaweed farmers or wives of male seaweed farmers in Sumenep Regency, 2) analyze the factors affecting the roles of those women to increase family income. The research employed quantitative and qualitative methods, using a questionnaire, in-depth interviews, focus group discussions, and observations as the means to collect the data. Most of them worked as day-based laborers for seaweed farming. The average income earned was IDR 585, 100/month. The domestic role of female seaweed farmers as housewives included cooking, taking care of the house, taking children to and picking them up from school, caring for children, and managing family finances. Work-hour, educational background, work experience, and the number of children as variables simultaneously affected the wives' income share on family income. However, work-hour as a variable did not have a significant effect on it.